Eksistensi Hukum Adat Dalam Pemerintahan Desa Batumiau Kecamatan Pulau Letti Kabupaten Maluku Barat Daya - Micael Ririhena; Yeheskel Wessy (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
The development of traditional villages is carried out by the Regent who is assisted by the Council for the Development of Traditional Institutions and the Board for the Development of Traditional Institutions. With the existence of various variations in the application of customs in the government system which gives rise to dualism in local leadership which in turn can result in ineffective village government, this is certainly food for thought for future village government systems. The research used is sociolegal research, namely a combination research method between doctrinal legal research methods and empirical legal research methods. Doctrinal research is intended to carry out library research by identifying laws and regulations and collecting other data related to the problem being studied. Empirical research is intended to identify, study and analyze the application of customary law in the administration of Batumiau village government, Pulau Letti District, Southwest Maluku Regency, as well as the impact of the application of customary law in the administration of village government. With the increasingly rapid flow of globalization, and the qualification that Southwest Maluku is a region famous for its culture and adherence to custom, it is appropriate that many are questioning the existence of customary law in this area for the future. Based on the description above, we are interested in conducting legal research with the title.